Study about the aplication of judo’s principles in their learning - Santos, Saray Giovana dos; Vieira, Lenamar Fiorese; Babata, Walter Kazunori; Ogawa, Celso Takeshi; Umeda, Osvaldo Yoshio (Journal of Physical Education (Maringá), 2008)
The aim of this study is to diagnose the applicability of the Judo’s Principles in the learning of Judo in the State of Paraná. Where it was observed the way that this principles had been tought to the Judo players and how they were applied in the practice in everyday life. On this research, 37 Judo players participated in the Senior’s Category, 46 in the Junior’s Category. There were also 10 trainers. All of them belong to the Paraná Judo Federation. Two questinnaires were used to measure them: one for trainers and another for players. This questionnaire was composed of opened and closed questions, and they were answered during the championships after weighing the players. This study lasted 19 months. After this period the results are: - That all trainers and players are concious that Judo has one philosophy. However they are not used to the knowledge of Judo’s principles that are the main aspects of this philosophy. - It wasn’t possible to determinate exactly the methodology applied for the trainers to transmit the Judo’s principles as long as they don’t used it correctly. - The Judo’s practice helped the practicers everyday life, mainly in their familiar relationship. Although when they are in the competition, they ignore all the philosophic aspects and the only objective is to win.